Non-interest activities affect the bank risk in the Asia Pacific region - Koh, Chin Wei; Ab Razak, Nazrul Hisyam; Kamarudin, Fakarudin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper’s main objective is to investigate whether the bank non-interest activities affect the bank risk between developed and developing markets in the Asia Pacific region banking sector over the years 2000-2015. We employ the pooled OLS and panel regression to assess the effect on bank risk through 61 representative banks from Australia, Hong Kong, Korea, Malaysia, Singapore and Thailand. We categorize Australia, Hong Kong and Singapore as developed countries while Malaysia, Korea, and Thailand as developing countries. The empirical findings indicate that the bank non-interest based activities do have overall impact on Asia Pacific banks’ risk. Once we further study by segregate into developed and developing countries segment, we only able to find that the impact do significant on developing countries only not on developed countries. We also find that the bank risk also affected by subprime crisis for Asia Pacific countries by factor in bank non-interest activities. The findings from this study are expected to contribute significantly toward decision-making for regulators, policymakers, bank managers, investors, and also to the existing knowledge on performance of the Asia Pacific banking sector.